Premarital Sexual Behaviours among Secondary School Adolescents: A Cross-sectional Study in Kathmandu - Upreti, Yadu Ram; Acharya, Devaraj (Journal of Health Promotion, 2020)
Young people’s sexuality is often stigmatized in South Asian societies, including Nepal, where premarital sex is not accepted socially and culturally. However, the prevalence of early sexual activities among adolescents has increased over time. Given this background, this paper aimed to explore the prevalence of premarital sexual behaviour among the urban high school adolescents. This study utilized a cross-sectional design and collected a total of 609 students of grade 9-12 [ages 10-19] from both community and institutional schools in the Kathmandu metropolis. A validated structured questionnaire was employed and data were analyzed using SPSS with version 24. Univariate, bivariate, and multivariate analyses were performed to interpret the results. The study showed that the mean age of the respondents was 16 years. More than half of adolescents (52.4%) ever watched pornography, amongst whom eight percent did it on a regular basis. Similarly, 14 percent of in-school adolescents ever experienced premarital vaginal sexual intercourse, where the median age for the sexual debut was 16 years. Male respondents tended to be 13 times more likely to have premarital sex compared to the girls. Respondents who were exposed to pornography materials were likely to be exposed by 5.7 times higher than that who were not. Further, 48 percent respondents who ever had sex did not use condoms during their first sexual intercourse, followed by 45 percent who had multiple sex partners.The study concluded that a notable proportion of adolescents was involved in premarital sexual behaviours followed with vaginal sexual intercourse, especially among the boy students. Hence, the results of this study suggest school-based comprehensive sexuality education to minimize the risky sexual behaviour and promote the safer sexual activities among the secondary level school adolescents.